Monopoly Legal Aspects of Violations in Determining Flight Transportation - Markus sihombing; Helvis Helvis (Penerbit Kemala Indonesia, 2021)
This study aims to find out how the Regulation of competition law in determining of air fares in Indonesia using normative judicial research methods. From the result it can be concluded:1. Law of the Republic Indonesia Number 5 of 1999 concerning the prohibition of monopolistic practices and unfair business competition. It enough to keep the business climate become conducive and away from of unfair business competition which can harm other parties. Thus, the state has carried out its function and responsibilities in accommodating the interests of its citizens. Furthermore, specifically regarding the flight itself. The government has also made regulations through the Law of the Republic of Indonesia Number 1 of 2009 concerning aviation.2. One of the government’s steps so that the implementation of law and regulation is carried out properly, the business competition supervisory commission. This content is the cancellation of the lower and upper limit of airfare and cargo by the national air carrier’s association (INACA in 2001). The cancelation of this tariff fixing makes aircraft fares more competitive, which in the end leads to a balance between the interests of entrepreneurs and businesses public.